Comparative Studies between Urbanization and Dam Settlement Processes - Poleto, Cristiano; Fernandes, Felippe (European Journal of Sustainable Development, 2018)
The city of Viamão is located in the metropolitan region of Porto Alegre, in the Rio Grande Sul State, southern Brazil. The Mãe d'Água dam was built in 1962 and, due to the lack of urban planning during the last forty years, received large discharges of sediments and contaminants (organic and/or inorganic). This study aimed to use the geochronology technique using the lead element 210 (210Pb) through the cores of sediments sampled from the Mãe D'água dam and to establish the chronology of the sedimentary layers over the last four decades, in addition to the characterization of the sedimentation processes in the Mãe D'Água reservoir and to size the sediment volumes silted in the reservoir in the current scenario, year 2014 (year of sampling) and thus, to present the total sediment concentrations during the 40-year silting. The sediment column, bathymetry, bibliographical references and GIS resources were used to infer the process of urbanization and sedimentation process of the dam, and representative samples were collected in June 2014, using sediment cores distributed in the dam area. The sediment cores were extracted through the "Piston core" sampler. With the results obtained, graphs and tables were generated to create the mathematical models and later the sedimentation maps, establishing correlations with the sedimentation geochronology studies during the last four decades (layers of sedimentation generated in each of these periods). There were periods with high sedimentation rates, mainly during the acceleration of the process of urbanization of the basin resulting in a total sediment volume of 44% of the useful volume of the project, which drastically reduces the capacity of the Mãe d'Água dam. Keywords: Urban dams, Sediments, Sedimentation of dams.